Ідентифікація користувачів англійської мови у діловому дискурсі - Наумова, Н. (Лексикографічний бюлетень, 2006)
The English language users’ identification in Business Discourse is studied diachronically.
Socio-pragmatic, discoursive and communicational parameters are considered.